Neural Representation of Subjective Sexual Arousal in Men and Women. Issue 10 (1st October 2016) - Parada, Mayte; Gérard, Marina; Larcher, Kevin; Dagher, Alain; Binik, Yitzchak M.
ABSTRACT: Introduction: Studies investigating brain indices of sexual arousal have begun to elucidate the brain's role in processing subjective arousal; however, most research has focused on men, used discrete ratings of subjective arousal, and used stimuli too short to induce significant arousal in women. Aim: To examine brain regions modulated by changes in subjective sexual arousal (SSA) rating intensity in men and women. Methods: Two groups (20 men, 20 women) viewed movie clips (erotic or humorous) while continuously evaluating changes in their SSA using a Likert-like scale (0 = not aroused, 10 = most aroused) and answering discrete questions about liking the movies and wanting sexual stimulation. Brain activity was measured using functional magnetic resonance imaging. Main Outcome Measures: Blood oxygen level-dependent responses and continuous and discrete measurements of sexual arousal. Results: Erotic movies induced significant SSA in men and women. No sex difference in mean SSA was found in response to the erotic movies on continuous or discrete measurements. Several brain regions were correlated with changes in SSA. Parametric modulation with rating intensity showed a specific group of regions within the parietal lobe that showed significant differences in activity among low, medium, and high SSA. Conclusion: Multiple regions were concordant with changes in SSA; however, a subset of regions in men and women was modulated by SSA intensity, a subset previously linked to attentional processes, monitoring of internal body representation, and processing of sensory information from the genitals. This study highlights that similar brain regions are activated during subjective assessment of sexual arousal in men and women. The data further highlight the fact that SSA is a complex phenomenon made up of multiple interoceptive and attentional processes.